A simple optical system delivering a tunable micrometer pink beam that can compensate for heat‐induced deformations. (8th June 2015) - Reininger, Ruben; Liu, Zunping; Doumy, Gilles; Young, Linda
<x xml:space="preserve">Abstract</x> The radiation from an undulator reflected from one or more optical elements (usually termed `pink‐beam') is used in photon‐hungry experiments. The optical elements serve as a high‐energy cutoff and for focusing purposes. One of the issues with this configuration is maintaining the focal spot dimension as the energy of the undulator is varied, since this changes the heat load absorbed by the first optical element. Finite‐element analyses of the power absorbed by a side water‐cooled mirror exposed to the radiation emitted by an undulator at the Advanced Photon Source (APS) and at the APS after the proposed upgrade (APSU) reveals that the mirror deformation is very close to a convex cylinder creating a virtual source closer to the mirror than the undulator source. Here a simple optical system is described based on a Kirkpatrick–Baez pair which keeps the focus size to less than 2 µm (in the APSU case) with a working distance of 350 mm despite the heat‐load‐induced change in source distance. Detailed ray tracings at several photon energies for both the APS and APSU show that slightly decreasing the angle of incidence on the mirrors corrects the change in the `virtual' position of the source. The system delivers more than 70% of the first undulator harmonic with very low higher‐orders contamination for energies between 5 and 10 keV.